Carlsbergia, a replacement name for Indiella Sautya, Tabachnick & Ingole, 2011 (Porifera: Aulocalycidae) - Gaudin, Jimmy (Zootaxa, 2019)
The genus Indiella was established by Sautya, Tabachnick & Ingole in 2011 to include the monotypic, and type species Indiella ridgenensis for a species of Porifera (Hexactinellida: Aulocalycidae) from the Carlsberg Ridge in the Indian Ocean. Unfortunately, it turns out that this name is already preoccupied by Indiella Blattný, 1925 (type species: Ctenistes birmanensis Motschulsky, 1851 by monotypy), a poorly known genus of Pselaphine beetle (Coleoptera: Staphylinidae). However, although Indiella Blattný is currently considered as a junior synonym of Sognorus Reitter, 1881, this name is available and, therefore, according to Article 52.2 of the International Code of Zoological Nomenclature (ICZN, 1999), Indiella Sautya, Tabachnick & Ingole, as a junior homonym, cannot be used. To resolve this homonymy, in accordance with Article 60 of the ICZN, a substitute name with a new combination is proposed below.